2016
DOI: 10.21082/jbio.v6n2.2010.p107-112
|View full text |Cite
|
Sign up to set email alerts
|

Kultur In Vitro Endosperma, Protokol yang Efisien untuk Mendapatkan Tanaman Triploid secara Langsung

Abstract: In Vitro Culture of Endosperm: An efficient protocol to propagate triploid plants directly. L. Agus Sukamto. Triploid plants are very vigorous and beneficial since they generally produce seedless fruits, bigger flowers, and produce more volume of wood than the diploid counterparts. The triploid plants can be produced by crossing diploid and tetraploid plants, but this method is cumbersome and takes a long time. In vitro culture of endosperm is an alternative method to produce triploid plants directly. The succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…Callus formation indicated that the explants could absorb nutrients from media. Furthermore, embryo explants are faster for callus and shoot formation [29]. The addition of the hormone 2 ppm 2,4-D and 0.5 ppm BAP can induce callus on the seeds of Kasturi Orange (Citrus macrocarpa) [30].…”
Section: Percentage Of Viable Explantsmentioning
confidence: 99%
“…Callus formation indicated that the explants could absorb nutrients from media. Furthermore, embryo explants are faster for callus and shoot formation [29]. The addition of the hormone 2 ppm 2,4-D and 0.5 ppm BAP can induce callus on the seeds of Kasturi Orange (Citrus macrocarpa) [30].…”
Section: Percentage Of Viable Explantsmentioning
confidence: 99%
“…Keberhasilan kultur endosperma dipengaruhi oleh beberapa faktor diantaranya umur endosperma yang dikultur dan penyertaan zigot embrio (Sukamto, 2010). Penentuan umur endosperma saat dikultur merupakan fase kritis terhadap respon pertumbuhannya (Tao et al 2009).…”
Section: Pembahasanunclassified
“…Endosperm culture is an alternative technique to produce triploid plants directly, only through one step [7]. The superiority of endosperm culture can produce triploid plants that have seedless or seedling but sterile [8]. The success of endosperm culture is influenced by the age of the endosperm, the formulation of the media, the germination of the resulting embryo, the age of the culture [8], and endogenous hormones and growth regulators (PGRs) added to the growing media.…”
Section: Introductionmentioning
confidence: 99%
“…The superiority of endosperm culture can produce triploid plants that have seedless or seedling but sterile [8]. The success of endosperm culture is influenced by the age of the endosperm, the formulation of the media, the germination of the resulting embryo, the age of the culture [8], and endogenous hormones and growth regulators (PGRs) added to the growing media. PGRs has an important role in controlling biological processes in plant tissues.…”
Section: Introductionmentioning
confidence: 99%